2020
DOI: 10.3390/v12091053
|View full text |Cite
|
Sign up to set email alerts
|

Structural Biology of Influenza Hemagglutinin: An Amaranthine Adventure

Abstract: Hemagglutinin (HA) glycoprotein is an important focus of influenza research due to its role in antigenic drift and shift, as well as its receptor binding and membrane fusion functions, which are indispensable for viral entry. Over the past four decades, X-ray crystallography has greatly facilitated our understanding of HA receptor binding, membrane fusion, and antigenicity. The recent advances in cryo-EM have further deepened our comprehension of HA biology. Since influenza HA constantly evolves in natural cir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 170 publications
(218 reference statements)
1
45
0
Order By: Relevance
“…In the crystal structures of the avian H5 HA and canine H3 HA complexed with avian-type receptor glycans 6-Su-3'SLN and 6-Su-SLe x , the side chain of K193 interacts with the sulfogroup attached to GlcNAc-3 (Collins et al, 2014;Xiong et al, 2013). In the H3N2/1968 HA complexes with human-type receptor analogues LSTc and 6SLN-LN, the side chain of S193 contacts the Gal-4 residue of the glycan (Eisen et al, 1997;Wu and Wilson, 2020). These observations suggest that substitution N193S affects binding avidity of HK by altering HA interactions with sub-terminal saccharide residues of both avian-type and human-type receptor glycans.…”
Section: Discussionmentioning
confidence: 99%
“…In the crystal structures of the avian H5 HA and canine H3 HA complexed with avian-type receptor glycans 6-Su-3'SLN and 6-Su-SLe x , the side chain of K193 interacts with the sulfogroup attached to GlcNAc-3 (Collins et al, 2014;Xiong et al, 2013). In the H3N2/1968 HA complexes with human-type receptor analogues LSTc and 6SLN-LN, the side chain of S193 contacts the Gal-4 residue of the glycan (Eisen et al, 1997;Wu and Wilson, 2020). These observations suggest that substitution N193S affects binding avidity of HK by altering HA interactions with sub-terminal saccharide residues of both avian-type and human-type receptor glycans.…”
Section: Discussionmentioning
confidence: 99%
“…The viral spike glycoprotein hemagglutinin currently serves as the primary seasonal influenza vaccine antigen, but also bears a number of conserved features which have been proposed as broadly protective ‘universal’ vaccine targets [ 1 , 4 , 31 , 34 , 35 , 94 , 95 ]. HA is a homotrimer consisting of a highly variable globular head domain (HA1 subunit) and a more conserved membrane proximal stalk region (HA2 subunit) [ 94 , 96 , 97 , 98 ]. Structurally resolved sites of vulnerability are described in detail below and include targets on both the head and stalk domains ( Figure 3 ).…”
Section: Functionally Conserved Antibody Targets On Influenza Hemamentioning
confidence: 99%
“…The next advance in 1988 was the structure of HA in complex with its receptor; the sialic acid receptor could then be visualized binding in a shallow receptor binding pocket at the apex of the HA trimer (PDB IDs: 5HMG, 4HMG) (128). Much of the history of influenza HA structural studies can be found in (129) and a recent update this year in (130).…”
Section: Antigen Structurementioning
confidence: 99%